Leprosy Resilience with Disabilities Due to Illness: A Qualitative Study - Atika Jatimi; Ah Yusuf; Sestu Retno Dwi Andayani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2020)
Introduction: Leprosy is an infectious disease that still causes complex problems. The problem in question is not only in medical and physical terms, such as disability, but extends to social, economic, and cultural problems. This study aims to explore the experience of leprosy sufferers with disabilities to achieve resilience. Methods: A descriptive qualitative research design with a phenomenological approach was used. The number of participants was eleven people affected by leprosy with grade 1 and 2 disabilities in Sumenep Regency obtained by a purposive sampling technique. Data collection used in-depth interviews with interview guides and field notes; the results of data collection were analyzed with theme analysis. Results: This study produced five main themes about the experience of leprosy patients in the process of achieving resilience, namely: 1) self-stigma as a stressor experienced by lepers, 2) psychosocial problems that arise in response to stressors, 3) active coping as a method of resolving stress, 4) positive adaptation as a form of self-adjustment, 5) characteristics of strong individuals. Conclusion: Lepers with disabilities identify self-stigma as a stressor that triggers the emergence of psychosocial problems. Individuals can form tough characteristics, such as responding positively to unexpected conditions, becoming more productive, and showing helping others behavior after overcoming stressors through the stages of active coping and positive adaptation.